(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
This paper focuses on using a stream of consciousness in James Joyce’s novel Ulysses. Stream of consciousness is a narrative technique that depicts the continuous flow of thoughts and sensations experienced by characters’ minds. In Ulysses, Joyce masterfully employs this technique to delve into the complex minds of his characters, Leopold Bloom and Stephen Dedalus. By abandoning traditional linear storytelling, Joyce captures the intricacies of human thought processes and immerses readers in the characters’ inner worlds. The novel’s structure and narrative style are characterized by interior monologue, associative thinking, and a fragmented structure. Through these techniques, Joyce offers readers a unique and intimate reading experience, exploring themes of identity, memory, time, and the depiction of Dublin. By embracing the stream of consciousness, Joyce pushes the boundaries of conventional storytelling, inviting readers to engage with his characters’ rich and intricate inner lives.